Cultural Ecosystem Services in Land Use/Land Cover Change: A Literature Review and Prospects for Future Research - Yu Pan; Yanbo Qu (Land)
The land use system, which is endowed with the most crucial and fundamental natural resources for human survival and development, plays a pivotal role within the entire ecosystem. In recent years, cultural ecosystem services (CESs) have also gradually garnered widespread attention. The study of cultural ecosystem services in the land use system plays a significant role in the rational utilization of land resources and the resolution of contradictions between land resources and sustainable development. This review, framed in Land Use/Land Cover Change (LUCC), applies keyword clustering and keyword evolution analysis to comprehensively review and synthesize academic literature on cultural ecosystem services. The analysis is organized into two dimensions: the overall study of cultural ecosystem services in LUCC and the study of specific categories of cultural ecosystem services in LUCC. Relevant papers from CNKI and WOS academic databases are included. The results show that the number of papers retrieved from WOS was significantly higher than the number retrieved from CNKI, while both databases exhibited a clear upward trend in the number of papers. It is worth noting that in the literature retrieval results for different types of land research, the majority of the papers focused on water, accounting for 51% and 44% of the totals in WOS and CNKI, respectively. Among these papers, research centered on recreation and ecotourism was the richest. Through this review, it was further revealed that research on cultural ecosystem services was initiated and has gradually developed into a relatively complete knowledge system. However, research on cultural ecosystem services in LUCC still requires further exploration, particularly in terms of assessment methods. This review thus highlights the need for future research to focus more on cultural ecosystem services in the land use system and to delve deeper into evaluating their values. By employing more scientific and rational approaches, land resources can be effectively managed and utilized to address challenges related to land resources and sustainable development.